A study on the factors that influencing the sales performance of Corporate Sales Unit (CSU) in M3 Technologies Asia Berhad (M3 Tech) between 2007-2009 / Mohd Syahryzal Awang Kechik - Awang Kechik, Mohd Syahryzal (Faculty of Business and Management, 2009)
From its early starts, M3 Technologies (Asia) Berhad (M3 Tech) formerly known as AKN Messaging Technologies Berhad (AKN MTECH) was incorporated in Malaysia on 6th May 1999 under the Companies Act 1965 as a private limited company as was subsequently converted to a public listed company on 20th June 2002. M3 TECH is the first mobile content and applications developer to be listed on the Malaysian Stock Exchange MESDAQ market (stockcode: M3Tech) in 2003. The company has offices in Malaysia, Thailand, Singapore, China, Indonesia, Hong Kong and Pakistan is a leading mobile content provider in Malaysia, which provides a wide range of consumer, enterprise and partnership products and services, and is making inroads to being the leader in this industry, regionally. Over the years, M3 TECH has been involved in providing interactive mobile solutions for many credible corporations including banks, securities firms, insurance companies, and education centers and media houses. Its regional subsidiaries have now also reached a mature level in their respective industries and reaping the fruits since incorporation. Each subsidiary is now at the forefront in their individual industry, ensuring the products offered compliments the technology trends and consumer demands. M3 TECH is focused on being a recognized leader in all its markets, delivering exceptional value to its customers and achieving sustainable growth in both local and international Markets. Even though the achievement of M3 TECH look excellent on the paper actually is not going well for the M3 TECH as a state’s measurement. It was the reason why the researcher does for this research study.